Protection Analysis Of Children Rights That Was Born From The Rape Causing (Study in State Court (PN) in Ex-Residency Cirebon Jurisdiction) - Endang Kusnandar; Anis Mashdurohatun; Siti Rodhiyah Dwi Istinah (Jurnal Daulat Hukum, 2020)
Criminal cases of rape very much creates difficulties in solving both at the stage of investigation, prosecution, or at the stage of the imposition of the verdict. The problems of this study are: forms of legal protection given to the rights of Children Which Born fom rape victims in Ex Residency Cirebon Jurisdiction and constraints in the implementation of the provision of legal protection against rape victims in Ex Residency Cirebon Jurisdiction and solutions.The method used by researchers is normative juridical law approach and specification in this study were included descriptive analysis. The source and type of data in this study are primary data obtained from field studies with interview members of the Police of Ciwaringin Cirebon, And secondary data obtained from the study of literature.Based on the results of research that as is the case in jurisdictions other areas, merely enacted regional regulation on Child Protection, but the regulation is not set up for a child born to mothers who were raped or pregnancy due to rape, as well as court decisions, no one has noticed the rape victims who become pregnant as a result of rape, either already known or unknown since the trial process after the imposition of the verdict (ponis), as well as the Agency duties and authorities are not up to provide protection to Children Which Born from rape, but the child of such status as well as victims. Obstacles such as the difficulty to obtain information from the victim because of the victim's mental condition of the child, still quite a lot of people who are reluctant to testify as a witness, investigators have no children, as well as the infrastructure is not yet complete. To overcome the obstacles faced by those already undertaken several measures, among others cooperate with relevant agencies to provide protection and assistance to child victims of rape, bring in psychologists to recover the child's mental disturbed for being a victim of rape cases, as well as trying to convince the witness that willing to give information and not to be afraid to provide testimony.Keywords : Rights Protection; Children; Rape.